Computer optimization in least square estimation program - Halim Setan, 1957-, author; Muhammad Asyran, author; Malaysian Science and Technology Congress (2005 : Kuala Lumpur) (Skudai : Universiti Teknologi Malaysia, 2005)
PSZJBL